2004
DOI: 10.1016/j.ydbio.2004.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between activator–inhibitor coupling and cell-matrix adhesion in a cellular automaton model for chondrogenic patterning

Abstract: We present a stochastic cellular automaton model for the behavior of limb bud precartilage mesenchymal cells undergoing chondrogenic patterning. This "agent-oriented" model represents cells by points on a lattice that obey rules motivated by experimental findings. The "cells" follow these rules as autonomous agents, interacting with other cells and with the microenvironments cell activities produce. The rules include random cell motion, production and lateral deposition of a substrate adhesion molecule (SAM, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 52 publications
0
50
2
Order By: Relevance
“…Further support comes from the diffuse presence of the dermal condensation marker NCAM (Jiang and Chuong, 1992) in ERK-suppressed specimens. This parallels the involvement of growth factors in regulating adhesion molecules during limb morphogenesis (Hentschel et al, 2004; Kiskowski et al, 2004). Using a localized bead source, we showed that FGF4 can specifically induce phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Further support comes from the diffuse presence of the dermal condensation marker NCAM (Jiang and Chuong, 1992) in ERK-suppressed specimens. This parallels the involvement of growth factors in regulating adhesion molecules during limb morphogenesis (Hentschel et al, 2004; Kiskowski et al, 2004). Using a localized bead source, we showed that FGF4 can specifically induce phosphorylation of ERK.…”
Section: Discussionmentioning
confidence: 54%
“…Mechanisms involving the reaction and diffusion of chemical substances and the chemotactic response of cells to such chemicals have been proposed for a number of biological phenomena including the pattern forming behavior of the slime mold, Dictyostelium discoidium (Vasiev, 1994) and the bacterium E. coli (Zorzano, 2005), patterns on the integument of snakes and fish (Myerscough, 1991; Painter, 1999), in the induction of hairs and feathers (Nagorcka and Mooney, 1992; Jung et al, 1998) and feather branching (Harris et al, 2005; Yu et al, 2005). These principles also have been used to explain skeletal patterning in the limb bud (Hentschel et al, 2004; Kiskowski et al, 2004; Miura and Maini, 2004). However, much remains to be learned about how molecular pathway and cellular events are coupled to the patterning process at the tissue / organ level.…”
Section: Introductionmentioning
confidence: 99%
“…Those that undergo condensation round up, reducing their surface area, but do not move away from adjacent noncondensing cells. Therefore, unlike the situation in the model of Kiskowski et al [26], mesenchymal condensation in micromass culture does not involve accumulation of cells at particular sites with concomitant depletion of cells in surrounding zones. (2) The representation of cells, morphogens, and ECM on a common grid is physically unrealistic.…”
Section: Introductionmentioning
confidence: 87%
“…In a previous study [26] we presented a discrete “biological lattice gas” model for high-density cultures of precartilage mesenchymal cells derived from the embryonic vertebrate limb. This model, which was based on the physical notion of a lattice gas, in which individual particles are free to move from point to point on a lattice at discrete time-steps, accurately simulated the formation of patterns of mesenchymal condensations observed in high-density micromass cultures of such cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation